Stock Repurchase by Tender Offer: An Analysis of the Causes of Common Stock Price Changes: Discussion - Downes, David (Journal of Finance, 1980)
David Downes, Stock Repurchase by Tender Offer: An Analysis of the Causes of Common Stock Price Changes: Discussion, The Journal of Finance, Vol. 35, No. 2, Papers and Proceedings Thirty-Eighth Annual Meeting American Finance Association, Atlanta, Georgia, December 28-30, 1979 (May, 1980), pp. 319-321